From Article 12b of the UN-MC to Article 7 of the Regulation 282/2011: Between Automaton and Minimal Human Involvement/Intervention - Dulevski, Stoycho (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The current article draws a comparison between one of the necessary criteria both for the electronically-supplied services (ESS) under Article 7 of the Council Implementing Regulation (EU) No. 282/2011 of 15 March 2011 laying down the implementing measures for the Directive 2006/112/EC on the common system of value added tax (Regulation 282/2011) as well as the automated digital services (ADS) under Article 12B of the United Nations Model Taxation Convention between Developed and Developing Countries (UN-MC). This is “minimal human involvement/intervention.” The aim is to outline the similarities and the differences between the approaches for their design, as well as the possible challenges therewith.